Pengembangan Alat Pendeteksi Kebocoran Liquefied Petroleum Gas dengan Metode Research and Development - Herfandi Herfandi (LPPM Universitas Dinamika Bangsa, 2022)
Indonesian people already use LPG (Liquefied Petroleum Gas) as the main fuel. LPG has a weakness in the material used is very flammable in air. LPG safety devices are currently ineffective because we cannot know the condition of LPG when we are not at home. The Research and Development method is able to produce and develop products that already exist today and have a high validity value, because they have passed various series of trials. This study develops an LPG leak detector using research and development methods. The result of this study is that the LPG leak detection tool has a call gateway notification feature on two user mobile numbers that have been setup on the microcontroller and have been tested using gas from matches and smoke. The limited test obtained an average score of 80 and is included in the good category, while the wider trial of the developed tool has proven to be more effective than the manual tool currently used. This gas leak detection tool is expected to be able to make it easier for the public to get early notification when an LPG leak occurs and immediately take preventive actions to prevent fires.